2016
DOI: 10.1210/jc.2015-4296
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Genetic, and Biochemical Characteristics of Early-Onset Diabetes in the Finnish Population

Abstract: Mutations in the K-ATP channel and INS genes were the most common cause of early diagnosed monogenic diabetes. After 6 months of age, patients with diabetes had high HLA risk genotypes and islet autoantibodies, reflecting the autoimmune character of diabetes in that age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Finally, these variants are likely to have a functional effect due to nonsense-mediated decay causing haploinsufficiency 12, 22 . This is further supported by the studies that showed that the homozygous RFX6 PTVs cause neonatal diabetes 15, 23, 24 . Among unknown MODY cases, RFX6 PTVs were responsible for 7.5% Finnish cases compared to only ~1% of non-Finnish European cases.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Finally, these variants are likely to have a functional effect due to nonsense-mediated decay causing haploinsufficiency 12, 22 . This is further supported by the studies that showed that the homozygous RFX6 PTVs cause neonatal diabetes 15, 23, 24 . Among unknown MODY cases, RFX6 PTVs were responsible for 7.5% Finnish cases compared to only ~1% of non-Finnish European cases.…”
Section: Discussionmentioning
confidence: 52%
“…29/47 were part of the discovery and replication cohorts. 18/47 were identified separately or had been previously reported 18, 23 (Supplementary Fig. 2 – Families 3–5, Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RFX6 PTVs were highly enriched in both discovery and replication cohorts compared to control cohorts, supporting their pathogenicity. The ExAC database has been very useful in identifying benign variants because of an unusually high frequency in the population compared to frequency of the disease in question 15,23,24 . However, caution is required for reduced penetrance variants as their frequency can be higher than estimated disease frequency in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…29/47 were part of the discovery and replication cohorts. 18/47 were identified separately or had been previously reported 18,23 (Supplementary Fig. 2–Family 3–5, Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%